Preseason anthropometric characterization of world level male futsal players and its correlation to performance - Chambel, C.; Rodrigues, F.; Monteiro, C. P.; Pereira, J. R.; Sousa, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Body composition is frequently monitored in elite sports to evaluate players` nutritional status and to understand muscle mass (MM) and fat mass (FM) fluctuations and their impact on physical performance. Futsal is an intermittent team sport, requiring players to develop speed and strength, which are positively influenced by MM, while being agile, which requires a moderately low FM percentage. The aim of this study was (i) to characterize the preseason body composition of elite male futsal players and (ii) to identify correlations between body composition and performance. Anthropometric assessment was carried out on 15 elite futsal players. Height, body weight (BW), 3 girths (relaxed arm, mid-thigh, and calf) and 8 skinfolds (biceps, triceps, subscapular, iliac crest, supraspinale, abdominal, front thigh, and medial calf) were measured according to the ISAK protocol. Muscle mass was calculated using Lee predictive equation (Lee RC et al. Am J Clin Nutr 2000, 72(3):796-803). Performance tests included 5, 10, 15 and 20-m sprints, 5-0-5 change of direction test, 10-5 repeated jump test, bench press, isometric mid-thigh pull, and countermovent jump (CMJ). The Shapiro-Wilk test was used to test normality of the outcome variables. Descriptive statistics and Pearson correlations were performed. Mean values were 77.0 (7.5) kg for BW, 34.3 (2.9) kg for MM, 10.8 (0.9) kg/m2 for muscle mass index, and 67.8 (22.0) mm for the sum of 8 skinfolds. Direct correlations were found between body composition and CMJ. Namely, BW and MM correlated with the peak propulsive force of CMJ (r=0.754, p=0.001; r=0.563, p = 0.029, respectively) and MM and muscle mass index correlated with CMJ peak velocity (r=0.537, p=0.039; r=0.558, p=0.031, respectively) and CMJ height (r=0.556, p=0.031; r=0.581, p=0.023, respectively). Although research on body composition standards for futsal players is scarce, these results are in line with published data on football and can be used to set goals for futsal players. Further anthropometric and performance assessments will be carried out to understand changes throughout the season.